PROFIL PASIEN DERMATITIS ATOPIK DI POLIKLINIK KULIT DAN KELAMIN RSUD ULIN BANJARMASIN TAHUN 2019-2021 - Hadiqo, Nafisatul; Hadi, Sukses; Sanyoto, Didik Dwi; Savitri, Dwiana; Rahmiati, Rahmiati (Homeostasis, 2023)
Atopic dermatitis is a chronic relapsing inflammatory skin disease with dry skin, redness, and pruritus.The morphology and location of the lesion are different in each phase. The study aims to determine the profile of atopic dermatitis. This reseach is a observational description method using patients medical record. The results of this study show of the 67 patients the highest percentage obtained the following results, the highest number of patient occurred in the age range of  ≥12 years as 44 patient (65,7%), female gender (55,2%), place of origin Banjarmasin (68,7%), students (23,9%), dominant lesion morphologiest in the infantile phase are erythematous papules (27,6%), vesicles (24,1%), excoriations (13,8%), and in the childhood phase are erythematous papules (21%), lichenification (21%), scales (21%), and in the adolescent and adult phases are erythematous papules (17,9%), lichenification (17,9%), scales (22,4%), the most common locations types of lesions in the infantile phase was facial (42,1%), and in the childhood phase was lower extremity (50%), and in the  adolescent and adult phases was lower extremity (35,5%). The most common types of medications used were antihistamines (38,3%) and topical corticosteroid (38,3%). The conclusions of this study is that the most of atopic dermatitis sufferers in 2019, age group ≥12  years, female gender, place of origin Banjarmasin, students, morphology and location of different lesions in each phase, treated with antihistamine and topical corticosteroid.